Nanoparticle Counting for PTI: The Dirty Tail Paradigm — A Pragmatic Proposal to Strongly Reduce Urban PN Pollution from Combustion Engine Fleets - A. Mayer; J. Czerwinski; Th. Lutz; F. Legerer; M. Wyser; P. Comte; L. Larsen; L. Rubino; K. Vasilatou; D. Engelmann; M. Knoll; H. Burtscher (Emission Control Science and Technology, 2025)

Contrasting responses of different mixotrophic protists to light and nutrient availability - Sebastiaan Koppelle; Marina Ivanković; Mia M. Bengtsson; Christian Preiler; Jef Huisman; Corina P. D. Brussaard; Julia C. Engelmann; Robert Ptáčník; Susanne Wilken (Limnology and Oceanography, 2024)
Mixotrophic protists are important members of aquatic microbial food webs where they can dominate bacterivory and strongly impact energy and nutrient flow. While light and nutrient availability are known to impact grazing rates by mixotrophs in laboratory studies, little is known about how changes in resource availability affect mixotrophic organisms in natural communities. Here, we performed a short‐term grazing assay using fluorescently labeled bacteria in a phosphorus‐limited subalpine mountain lake to test how the availability of light and nutrients affect mixotroph grazing rates. High grazing rates by a Pseudopedinella ‐like dictyochophyte were unaffected by nutrient or light manipulation. In contrast, grazing rates by pigmented cryptophytes significantly decreased upon phosphorus addition, light deprivation, and a combination of both. We compare these findings with the seasonal analysis of a 4‐yr time‐series dataset of 18S rRNA gene amplicon abundances. While cryptophytes dominated in autumn and winter and were negatively related with water column stability, Pseudopedinella amplicon abundances showed a consistent spring–summer peak and were positively related with chlorophyll a concentrations. These results demonstrate the diversity in nutritional strategies among co‐occurring mixotrophic protists, which cannot be resolved by quantification of bulk grazing rates. Moreover, these different strategies result in distinct seasonal dynamics and coexistence of different mixotrophs, suggesting their respective trajectories into future aquatic ecosystems will also differ.

The role of phase transition by inception and surface reactions for the synthesis of silicon nanoparticles in a hot-wall reactor – Simulation and experiment - P. Wollny; L. Engelmann; M. Loewenich; I. Rahinov; H. Wiggers; C. Schulz; A. Kempf; I. Wlokas (Chemical Engineering Journal, 2023)

The role of phase transition by nucleation, condensation, and evaporation for the synthesis of silicon nanoparticles in a microwave plasma reactor — Simulation and experiment - P. Wollny; J. Menser; L. Engelmann; J. Sellmann; C. Schulz; H. Wiggers; A. Kempf; I. Wlokas (Chemical Engineering Journal, 2023)

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

A simple protocol for cryopreservation of zygotic embryos of ten accessions of coconut (Cocos nucifera L.) - O. N’Nan; M. Borges; J.-L. Konan Konan; V. Hocher; J.-L. Verdeil; J. Tregear; A. S. P. N’guetta; F. Engelmann; B. Malaurie (In Vitro Cellular & Developmental Biology - Plant, 2012)

Platinum anticancer agents and antidepressants: desipramine enhances platinum-based cytotoxicity in human colon cancer cells - Peyman Kabolizadeh; Brigitte J. Engelmann; Nicholas Pullen; Jennifer K. Stewart; John J. Ryan; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2012)

Object localization through the lateral line system of fish: theory and experiment - Julie Goulet; Jacob Engelmann; Boris P. Chagnaud; Jan-Moritz P. Franosch; Maria D. Suttner; J. Leo van Hemmen (Journal of Comparative Physiology A, 2008)

Evolution of C4 phosphoenolpyruvate carboxylase in the genus Alternanthera: gene families and the enzymatic characteristics of the C4 isozyme and its orthologues in C3 and C3/C4 Alternantheras - U. Gowik; S. Engelmann; O. E. Bläsing; A. S. Raghavendra; P. Westhoff (Planta, 2006)

A proteomic approach to understanding the development of multidrug-resistant Candida albicans strains - H. Kusch; K. Biswas; S. Schwanfelder; S. Engelmann; P. D. Rogers; M. Hecker; J. Morschhäuser (Molecular Genetics and Genomics, 2004)

Earthworm leukocyte populations specifically harbor lysosomal enzymes that may respond to bacterial challenge - P. Engelmann; L. Molnr; L. Plinks; E. L. Cooper; P. Nmeth (Cell and Tissue Research, 2004)